The Influence of Experiential Marketing on Customer Loyalty Mediated by Customer Satisfaction - Bramantoko, Beda; Maridjo, Herry (Journal of World Science, 2024)
The research aims to analyze the influence of Sense, feel, think, and act and relate to customer loyalty mediated by customer satisfaction. The research sample was 412 Uniqlo fast fashion customers using non-probability sampling techniques. The data collection technique uses a questionnaire. The data analysis technique uses Structural Equation Modeling (SEM) with the SmartPLS Version 4 application. The research results found that (1) sense and relate directly have a positive effect on customer loyalty, (2) feel, think, and act do not directly have an effect on customer loyalty, (3) sense and relate affect loyalty, partially mediated by job satisfaction, and (4) feel, think, and act have no effect on customer loyalty and are fully mediated by customer satisfaction. The influence of experiential marketing on customer loyalty mediated by customer satisfaction can predict success by more than ninety percent. This research has implications for understanding the factors that influence customer loyalty in the context of fast fashion, especially for Uniqlo. The research findings emphasize the significant direct influence of Sense and relate to customer loyalty, providing insight into the aspects that play an essential role in building and maintaining customer loyalty. Additionally, the mediating role of job satisfaction and customer satisfaction provides insight into the mechanisms underlying the relationship of experimental marketing elements with loyalty. Practically, these insights can guide marketers and managers in designing strategies to increase customer loyalty through targeted experimental marketing efforts.